Efeitos do metabolismo de probióticos na bioacessibilidade e capacidade antioxidante dos compostos fenólicos de Hylocereus Polyrhizus (pitaya vermelha) - Morais, Suênia Gabriela Gonçalves (2019)
The red pitaya (Hylocereus polyrhizus) is a fruit original from Mexico and Central and South America, widespread in tropical and subtropical regions. Red pitaya has considerable contents contents of phenolic compounds with recognized antioxidant activity. The interaction between phenolic compounds and probiotic bacteria have attracted the interest of the scientific community, because through transformations more active forms of these compounds may be obtained. The aim of the present study was to assess the effects of L. acidophilus LA-05 and B. lactis BB-12 on the content, bioaccessibility of the compounds phenolics and antioxidant capacity of the dialyzed fraction in red pitaya. For this, viable counts and parameters associated to the metabolism of the test probiotic strains were assessed after 48 h-cultivation in red pitaya. The survival of L. acidophilus LA-05 e B. lactis BB-12 in fermented red pitaya under simulated gastrointestinal conditions, as well as the effects of the metabolism of these strains on the content and bioaccessibility of phenolic compounds in red pitaya using a digestion model coupled with a simulated intestinal barrier were also determined. The bioaccessible fraction of the red pitaya fermented by the test strains was evaluated for the oxygen radical absorption capacity. After 48 h of incubation in red pitaya, the initial viable counts (approximately 7 log CFU/mL) of L. acidophilus LA-05 and B. lactis BB-12 increased (p < 0.05) 1.59 ± 0.18 and 1.43 ± 0.15 log CFU/mL respectively. At the same time, the sugar and pH contents decreased (p < 0.05), while the organic acid content increased (p <0.05). After exposure to simulated gastrointestinal conditions, viable counts of L. acidophilus LA-05 and B. lactis BB-12 in fermented red pitaya were around 8 and 7 log CFU/mL, respectively. In general, fermentation with probiotic strains decreased (p < 0.05) the content of most phenolic acids and flavonoids in red pitaya. L. acidophilus LA-05 increased (p < 0.05) the content of chlorogenic, gallic and syringic acids, cyanidin 3,5-diglucoside, procyanidin B1 and procyanidin B2, quercetin and rutin in the non dialyzed (non-absorbable) fraction while B. lactis BB-12 increased (p < 0.05) the content of caffeic, chlorogenic and syringic acids and procyanidin B1 in this same fraction. The bioaccessibility of caffeic acid, catechin, epigallocatechin gallate, kaempferol 3-glucoside, procyanidin B1 and procyanidin B2 increased (p < 0.05) in the red pitaya fermented by L. acidophilus LA-05. Increases (p < 0.05) in the bioaccessibility of catechin, epigallocatechin gallate and procyanidin B2 were also observed in the red pitaya fermented by B. lactis BB-12. The bioaccessible fraction of the red pitaya fermented by L. acidophilus LA-05 or B. lactis BB-12 showed higher antioxidant activity then than that obtained from the non-fermented red pitaya. These results show the impact of L. acidophilus LA-05 and B. lactis BB-12 on phenolic compounds in the red pitaya and suggest that these microorganisms may be used as an alternative to enhance the antioxidant potential of this fruit beside an increase of phenolic contents available in the non dialyzed fraction.